Relationships between neurodivergence status and adverse childhood experiences, and impacts on health, wellbeing, and criminal justice outcomes: findings from a regional household survey study in England - Charley Wilson; Nadia Butler; Zara Quigg; David Moore; Mark Bellis (BMC Medicine)
Abstract Background Evidence indicates that neurodivergent (ND) populations may be more at risk of experiencing adverse childhood experiences (ACEs), compared to neurotypical (NT) populations. However, this evidence has typically not examined a comprehensive set of ACEs and has only included ND individuals on the basis that they have a diagnosis. Very little research has examined the impacts of ACEs on negative adulthood outcomes for ND populations. The current study aimed to examine the associations between neurodivergence and experiences of ACEs, and the impact of being ND and experiencing ACEs on health, wellbeing, and criminal justice outcomes. Methods From November 2023 to April 2024, a household survey using representative sampling was undertaken with 5395 residents of an English region aged 18 + years. Neurodivergence status was measured using one self-report item. Nine ACEs were measured using validated self-report items. Outcome measures included: poor general health, low mental wellbeing, ever being arrested, and ever being incarcerated. Multinomial regression models were used to examine relationships between neurodivergence status and ACEs. Binary logistic regression models were used to examine independent relationships between neurodivergence status and ACE count and each outcome measure. Generalised linear models with an estimated marginal means function were used to estimate the increased risk of each outcome for different combinations of neurodivergence and ACE count status (NT less than four ACEs (reference group), NT 4 + ACEs, ND less than four ACEs, ND 4 + ACEs). Results A higher proportion of ND individuals experienced each ACE type than NT individuals. While controlling for sociodemographics, ND individuals were more likely to experience a greater number of ACEs than their NT peers. While controlling for sociodemographics, each outcome measure was more likely amongst those who were ND, and each outcome measure except for poor general health was more likely amongst those with higher ACE counts. Conclusions The combination of being ND and experiencing ACEs could additively increase risks of experiencing poor wellbeing and criminal justice outcomes by a greater extent than expected. Preventing and responding to ACEs in ND populations should be a priority to reduce risks of poor health, wellbeing, and criminal justice outcomes in this population.